PENGARUH PERSEPSI HARGA TERHADAP KEPUTUSAN PENYEWAAN TANAMAN HIAS PADA TUNAS MANDIRI FLOWERS&LANSCAPE DI PEKANBARU - -, Desi Susanti (LPPM Universitas Muhammadiyah Sumatera Barat, 2018)
This study aimeds to determine the influence of price perceptions on the decision ofornamental plant rental on Tunas Mandiri Flowers & Lanscape in Pekanbaru. Demand forrental ornamental plants because consumers wanted the place remains beautiful but do notwant to waist their time with maintaining the plants, hiriing gardeners and so forth. Thus, therental of ornamental plants to be an alternative selected by some consumers who want tobeautify their home or the place where they work. Tunas Mandiri Flowers & Lancsape wasone that took the opportunity. Demand for the rental of ornamental plants varied from thechoice of ornamental plant packages, the duration of leasing, and the choice of plant functionsand the price offered. Pricing offered by Tunas Mandiri Flowers & Lanscape could affectconsumer decisions. Every consumer had a different price perception to the ornamental plantsto be purchased. The population and sample in this study were all customers ofTunas Mandiri Flowers & Lanscape. There were 46 customers, from offices, hotels untilindividuals. Data analysis used quantitative descriptive analysis and simple linear regressionusing SPSS 21.0 for windows. The results obtained t value> t table (18,167> 2.015). Fromthese results it could be concluded that the perception of the price affected the decision ofornamental plants lease on Tunas Mandiri Flowers & Lanscape in Pekanbaru. The value ofcoefficient of determination (r square) obtained by 0.833. This means that 83.3% of thevariation in consumer decision variables could be explained by the variable of priceperception, while the remaining 16.7% was explained by other variables not proposed in thisstudy.Keywords: Price Perception, Consumer Decision